2003
DOI: 10.1111/j.1349-7006.2003.tb01438.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor regression by combined immunotherapy and hyperthermia using magnetic nanoparticles in an experimental subcutaneous murine melanoma

Abstract: Immunotherapy (IT) has become an accepted therapeutic modality. We previously reported that intracellular hyperthermia (IH) using magnetic nanoparticles induces antitumor immunity. We undertook these studies in order to study the combined effects of IT and IH on melanoma. Magnetite cationic liposomes (MCLs) have a positive surface charge and generate heat in an alternating magnetic field (AMF) due to hysteresis loss. MCLs were injected into a B16 melanoma nodule in C57BL/6 mice, which were subjected to AMF for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
121
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(128 citation statements)
references
References 38 publications
3
121
0
4
Order By: Relevance
“…We previously studied the H-2K b amount on B16 cells by flow cytometry. 39 Flow cytometric analysis using the anti-mouse H-2K b antibody revealed that B16 cells used in this study expressed a much lower amount of MHC class I antigen when compared with EL4 cells. In this study, we used poorly immunogenic B16 cells to assess the preclinical feasibility of a novel cancer therapy.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…We previously studied the H-2K b amount on B16 cells by flow cytometry. 39 Flow cytometric analysis using the anti-mouse H-2K b antibody revealed that B16 cells used in this study expressed a much lower amount of MHC class I antigen when compared with EL4 cells. In this study, we used poorly immunogenic B16 cells to assess the preclinical feasibility of a novel cancer therapy.…”
Section: Discussionmentioning
confidence: 65%
“…We previously reported that MCL-induced hyperthermia treatment at 43°C for 30 min induced necrotic cell death in B16 melanoma. 39 In this study, apoptosis detection assay by the terminal deoxynucreotidyl transferase (TdT)-mediated dUTP nick end labeling (TUNEL) method was performed, but no significant number of apoptotic cells was observed (data not shown). On the other hand, conventional hyperthermia systems are applied to induce apoptosis, not necrotic cell death.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In this case, the destruction or elimination of tumors would occur by increasing the tumor temperature typically within the range of 37-45 C for hyperthermia (1,2,5) or above 45 C for thermoablation, (3). In previous work, the heat has been induced using chemically synthesized nanoparticles, mainly in the form superparamagnetic iron oxide nanoparticles (SPION), which were either mixed in solution or mixed with cells or administered to a living organism (1)(2)(3)(4)(5)(6)(7)(8). The anti-tumoral activity of these heated nanoparticles has been evaluated both on animal models and clinically on humans (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%